2004
DOI: 10.1111/j.1468-1331.2004.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Early sympathetic hyperactivity in Huntington's disease

Abstract: To investigate whether Huntington's disease (HD) affects autonomic nervous system (ANS) functioning 33 subjects with positive genetic test results were studied. The subjects were classified according to Shoulson and Fahn (S&F) HD disability scale into three subgroups: subgroup 1 (eight asymptomatic gene carriers), subgroup 2 (13 mildly disabled HD patients) and subgroup 3 (eight moderately and four severely disabled HD patients). A battery of cardiovascular autonomic tests (Valsalva maneuver, deep breathing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 30 publications
4
77
0
3
Order By: Relevance
“…We, therefore, hypothesized that the changes in the cardiovascular ANS functioning could be detected as early as in the presymptomatic phase of the disease due to the successive involvement of the higher order parts of CAN. The common cardiovascular tests like the Valsalva manoeuvre, deep breathing and orthostatic test did not confirm the differences between PHD and EHD subjects [5,20]. In the present study we introduced new tests that could show more subtle differences in ANS function in PHD and EHD subjects.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…We, therefore, hypothesized that the changes in the cardiovascular ANS functioning could be detected as early as in the presymptomatic phase of the disease due to the successive involvement of the higher order parts of CAN. The common cardiovascular tests like the Valsalva manoeuvre, deep breathing and orthostatic test did not confirm the differences between PHD and EHD subjects [5,20]. In the present study we introduced new tests that could show more subtle differences in ANS function in PHD and EHD subjects.…”
Section: Introductionmentioning
confidence: 59%
“…Nevertheless, only a few studies on ANS function in presymptomatic and early symptomatic HD patients have been performed. Sympathetic predominance was found in presymptomatic and mildly and moderately affected HD patients [20], but another study [5] found no difference in LF and HF values between control, PHD and EHD group. Reasons for the discrepancies might be subtle ANS changes, different clinical methods of evaluation, differences in sample size and individual differences in disease onset and progression.…”
Section: Discussionmentioning
confidence: 95%
“…HF is among the leading causes of death in Huntington disease 114 , and the prevalence of HF in patients with Huntington disease is markedly increased com pared with age matched controls 115 [118][119][120] have demonstrated that whole body expression of polyQ proteins precipitates cardiomyopathy. Although this observation supports a direct involvement of the mutant huntingtin in development of cardiac disease, Huntington disease also features marked imbalance in the autonomic nervous system, leading to enhanced sympathetic tonus 121 , which might (partly) contribute to HF in Huntington disease. Data on the other ~30 proteopathies are even more inconclusive.…”
Section: Derailment Owing To Genetic Mutationsmentioning
confidence: 79%
“…L-phenylalanine is a precursor of tyrosine, therefore making L-phenylalanine also precursor of these catecholamine neurotransmitters. Hyperactivity of the sympathetic nervous system has been reported in HD sufferers 40 , and it could be speculated that increased neurotransmitter biosynthesis leads to depletion of tyrosine and L-phenylalanine precursors in both the frontal lobe and striatum.…”
Section: Resultsmentioning
confidence: 99%
“…The unaffected range is (CAG)6-35 repeats, alleles of (CAG)>40 are considered fully penetrant and these individuals carry a 100 % lifetime risk of developing HD and CAG repeat size with alleles of (CAG)>60 causes juvenile onset. Although HD can present itself at any age, the age of onset is typically [40][41][42][43][44][45] years with death typically occurring 15-20 years after the initial manifestation 3,9-11 . Currently there is no neuroprotective therapy 3 or ultimate "cure" for this debilitating neurodegenerative disease 5,8 .…”
Section: Introductionmentioning
confidence: 99%